Effect of Wheat Replacement by Pulse Flours on the Texture, Color, and Sensorial Characteristics of Crackers: Flash Profile Analysis - Danai Ioanna Koukoumaki; Konstantinos Giannoutsos; Putu Virgina Partha Devanthi; Panagiotis Karmiris; Sophia Bourni; Anastasia Monemvasioti; Vassiliki Psimouli; Dimitris Sarris; Konstantinos Gkatzionis (International Journal of Food Science)
Pulse flours are growing in popularity as alternatives to wheat in bakery products due to their high protein and nutritional value. However, the effect of different pulse species and substitution on sensory perception is unclear. The sensory perception of crackers made by partially replacing wheat with chickpea (40-80%) and lupin flour (10-30%) was evaluated using Flash profile analysis in association with instrumental analysis of texture and color. Flash profile analysis was conducted in Greece and Indonesia in order to allow culture comparison of the profiling of the samples and language by the subjects of the panel. Lightness (L∗) and hardness of crackers were decreased by the addition of pulses. Flash profile analysis indicated an association among color, texture, and sensory perception by judges. Derived attributes were associated with the physicochemical characteristics and raw materials of crackers for both panels. GPA analysis of Greek panel indicated that increasing the replacement of wheat led to the generation of more attributes regardless of pulse species, while the Indonesian panel was able to detect differences among pulse species.